Design process and rapid prototyping of animated music visualizations - Almeida, Horhanna; Cabral, Giordano; Moura, Rute (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19435, 2021)
The production of animations for Musical Information Visualization is still scarce and has challenges in the way of visually communicating information. Due to the need for domains of editing software, demanding technical skills and specific knowledge related to each area: animation, music, design and computing. In this article, we present a systematic review of the animated visualization area and, based on its conception processes, we elaborate an experimental model for the creation, prototyping and construction of musical animations. And through sessions developing quick prototypes, where we obtained qualitative results with feedback collection. We conclude that the importance of animation is exceptional, as an ally in the process of designing and creating a musical visualization, as it facilitates the representation of time to communicate structural elements of music, as they are dynamically arranged in a graphic area.